O princípio esperança e o movimento de multidão de 2013 - Douglas M. R. Porto (Ciências Sociais Unisinos)
In this article we investigated the importance of the expectant affection hope for the multitude movement that started in 2013 in the city of Porto Alegre/RS. Our main goal is to investigate the manner in which hope motivated the protesters’ actions and structured the manifestations. This goal seeks to answer the following question: how did hope motivated the 2013 manifestations in the city of Porto Alegre? Our methodology is qualitative, in which we used the analysis of journalistic photographic records of the 2013 manifestations – collected on news websites. We found, from that, that hope had crystallized in the factual reality, motivating the protesters to act through iconoclastic and softs practices, made it possible for the acts to intensify after the police repressions, connected the protesters intersubjectively around utopian objects and caused the temporary transfer of the social front from the interior of the state to the streets of the city.